2016
DOI: 10.1292/jvms.15-0572
|View full text |Cite
|
Sign up to set email alerts
|

Anti-NDV activity of baicalin from a traditional Chinese medicine <i>in vitro</i>

Abstract: The purpose of this study was to investigate the anti-Newcastle disease virus (NDV) activities of baicalin from Scutellaria baicalensis, a Traditional Chinese Medicine in vitro. Chicken embryo fibroblasts (CEFs) were infected with NDV, and quantitative analysis of apoptotic cells was performed using flow cytometry. Cytotoxicity and anti-viral activities of baicalin were studied using the MTT method. The results showed that the maximal safe concentrations of baicalin to CEFs was 1 × 2−2 mg/ml. Baicalin could di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 31 publications
0
17
0
1
Order By: Relevance
“…For example, out of 22 different flavonoids, six phytochemicals (apigenin, baicalein, biochanin A, kaempferol, luteolin, naringenin) were active against the avian influenza H5N1 virus in human lung epithelial (A549) cells through inhibiting nucleoprotein production [67]. Baicalin (the glucuronide of baicalein) was also active against a wide range of viruses, including enterovirus [68], dengue virus [69], respiratory syncytial virus [70], Newcastle disease virus [71], human immunodeficiency virus [72], and hepatitis B virus [73], and different mechanisms were suggested for its antiviral actions. For example, baicalin inhibits the production of HBV, the templates for viral proteins and HBV-DNA synthesis [73], and decreases IL-6 and IL-8 production without affecting IP-10 levels, as shown in a study on avian influenza H5N1 virus [67].…”
Section: Antiviral Medicinal Plants and Phytochemicalsmentioning
confidence: 99%
“…For example, out of 22 different flavonoids, six phytochemicals (apigenin, baicalein, biochanin A, kaempferol, luteolin, naringenin) were active against the avian influenza H5N1 virus in human lung epithelial (A549) cells through inhibiting nucleoprotein production [67]. Baicalin (the glucuronide of baicalein) was also active against a wide range of viruses, including enterovirus [68], dengue virus [69], respiratory syncytial virus [70], Newcastle disease virus [71], human immunodeficiency virus [72], and hepatitis B virus [73], and different mechanisms were suggested for its antiviral actions. For example, baicalin inhibits the production of HBV, the templates for viral proteins and HBV-DNA synthesis [73], and decreases IL-6 and IL-8 production without affecting IP-10 levels, as shown in a study on avian influenza H5N1 virus [67].…”
Section: Antiviral Medicinal Plants and Phytochemicalsmentioning
confidence: 99%
“…The chemical structure of BA has been determined 35 . BA possesses important functions, including anti-inflammatory 36 38 , anti-microbial 39 , 40 , and anti-oxidant activities 41 , 42 . Previous studies demonstrated that BA could reduce ROS production, suppress apoptosis, and inhibit the activation of the NF-κB and NLRP3 inflammasome signaling pathway in piglet mononuclear phagocytes treated with H. parasuis 34 .…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that different TCM may share the same antiviral mechanism. Published study has shown that baicalin can inhibit the NDV infection by blocking HN binding to sialic acid-containing receptors and virus adsorption [6], however we do not know how baicalin affects the spread of MDV from cell to cell yet as the mechanism of how MDV enters the host cells is lacking.…”
Section: Discussionmentioning
confidence: 96%
“…In recent years, the research on antiviral property of Traditional Chinese Medicine has attracted the attention of research groups worldwide due to its minimal side effect and low toxicity [11]. The baicalin as a avonoid is the metabolite of baicalein and the evidence of its antiviral role against HSV-1, HSV-2, ZIKV, IAV, DHAV-1, and NDV has been reported [4], [5], [6], [12], [13]. In our previous study, we demonstrated that baicalin has an speci c inhibitory effect on ALV-J infection by reducing the infectivity and affecting virus internalization [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation